Every dog has his day [large type] - Thompson, Janice A. (Gone to the dogs mysteries, 2023)
"Lone Star groomer, Isabel Fuentes, agrees to foster a feisty rescued dachshund, and the two are inseparable . . . until the new Texans quarterback, Corey Wallis, announces a large reward for his missing female dachshund. Suddenly all of Houston are on the lookout for the MIA pooch that bears a strong resemblance to Isabel's new pup. Corey makes arrangements to come to Lone Star clinic to pick up the dog, but he arrives without any proof of ownership and the clinic can't just hand over the dog. When the dachshund, Ginger, suddenly goes missing, Isabel is convinced Corey and his agent took her for a publicity stunt. Then there is a reporter who could be trying to manufacture a great story, and a cameraman seeking the big reward. Can there be a happy ending for Ginger?"--